Analysis of the Implementation of Total Quality Management (Tqm) on Nurse Performance at Mother and Child Hospital (Rsia) Eria Bunda Pekanbaru - Nurafni Marissa; Budi Hartono; Lita; Doni Jepisah; Arnawilis (Science Midwifery, 2022)
Total Quality Management (TQM) is an approach that is widely used by companies in improving quality with the aim of improving performance in quality, productivity and probability. That study aims to determine the application of TQM to the performance of nurse at RSIA Eria Bunda Pekanbaru in 2021. This study includes a quantitative study with a cross sectional design. The number of samples was carried out using a total sampling technique, namely 37 people. The analysis used chi square test, fisher exact test, multiple logistic regression and importance performance analysis (IPA) methods. The result showed that the focus on customers (OR:7.583 95%Cl=1.737-33.089), obsession with quality (OR:1500 95%Cl=0.220-10.218), scientific approach (OR:5.818 95%Cl=1.032-32.793 ), long term commitment (OR:5.993 95%Cl=1.337-25.226), teamwork (OR:7. 585 95Cl%Cl=1738-33.089), continuous improvement (OR:5.893 95%Cl=1.337-25.226), training education (OR: 3.405 95%Cl=0.879-13.188), freedom of control (OR:7500 95%Cl =1.715-32.796), unity of purpose (OR:0.941 95%Cl=0.118-7.499), involvement and empowerment (OR:10.625 95%Cl=1.874-60.246). The conclusion is that there is an influence between TQM focus on customers, scientific approach, long term commitment, teamwork, continuous improvement, education training, freedom of control and involvement and empowerment